Highlights from the 1st ISCB Latin American Student Council Symposium 2014. Issue 8 (December 2015) - Parra, R; Simonetti, Franco; Hasenahuer, Marcia; Olguin-Orellana, Gabriel; Shanmugam, Avinash
Abstract This report summarizes the scientific content and activities of the first edition of the Latin American Symposium organized by the Student Council of the International Society for Computational Biology (ISCB), held in conjunction with the Third Latin American conference from the International Society for Computational Biology (ISCB-LA 2014) in Belo Horizonte, Brazil, on October 27, 2014.